Compositional analysis of june beetle (Leucopholis irrorata chevrolat) II. Physico-chemical properties and mineral content - Naguit, Cherrielyne Enriquez; Dumelod, Benelyn Domingo (2000)
ABSTRACT Composition analyses were done on the raw, preprocessed, cooked and frozen samples of June beetle (Leucopholis irrorata Chevrolat). Various physico-chemical properties including length, width, weight, color, pH, titrable acidity and water activity were also analyzed. Amounts of fourteen minerals-calcium, chromium, copper, cobalt, iron, lead, manganese, potassium, sodium, zinc, phosphorus, and chloride were also studied. Analysis of Variance (ANOVA) and Duncan's Multiple Range Test (DMRT) were employed and the Standard Error of the Mean (SEM) calculated. Significant reductions in length and width were observed in the preprocessed and cooked samples. Weight varied greatly depending on the degree of the processing technique. Freezing storage decreased the lenght, width, and weight to some extent. There was no considerable change in color, however, a shift in value towards blackness was noticed in the preprocessed and cooked samples. Preprocessing lowered the pH and increased the predominant acid in the the sample. Similar effect was noticed in the cooked sample but the decreased in pH and increase in titrable acidity were not as remarkable as that of the preprocessed. The frozen sample had a considerable higher pH and lower titrable acidity than the three samples. Water activity decreased as the degree of processing increased. The minerals were analyzed using Atomic Absorption Spectrophotometry, except for phosphorus which was quantitated using the Molybdovanadophosphate nethod and chloride that was determined by the Mohr titration of salt. There was no specific trend for the gains and losses at different stages of processing. The cooked sample contained appreciable amounts of chromium and copper. Sodium and chloride were remarkably increased in the preprocessed and cooked samples. Iron, manganese, potassium, zinc and phosphorus significantly decreased in the cooked samples.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Edible insects; Beetles -- Analysis